2019
DOI: 10.3390/su11215959
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Differences in China’s Population Aging and Influencing Factors: The Perspectives of Spatial Dependence and Spatial Heterogeneity

Abstract: Since China became an aging society in 2000, the regional inequality of population aging has been highlighted, and the phenomenon of "aging before getting rich" has gradually become a core issue in China's coordinated socioeconomic development. This paper aims to comprehensively assess the spatial differences and driving forces of China's population aging through two-stage nested Theil decomposition, ESDA, and spatial econometric models. Empirical results show that spatial differences in population aging were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…First, the spatial distribution pattern of population aging has been investigated by extensive studies, and a positive spatial autocorrelation was found at the global level [ 9 ] and the country level such as Japan [ 11 ], South Korea [ 12 ], Italy [ 49 ], and China [ 25 ]. Those papers indicated that the population showed wide-ranging multiplicity and place specificity with complex spatial-temporal processes [ 50 ], and the aging population between regions can be attributed to their proximity to one another [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the spatial distribution pattern of population aging has been investigated by extensive studies, and a positive spatial autocorrelation was found at the global level [ 9 ] and the country level such as Japan [ 11 ], South Korea [ 12 ], Italy [ 49 ], and China [ 25 ]. Those papers indicated that the population showed wide-ranging multiplicity and place specificity with complex spatial-temporal processes [ 50 ], and the aging population between regions can be attributed to their proximity to one another [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated population aging process may place a heavy burden on China's social security and economic systems, thus, maintaining the well-being of an elderly population has become a major concern for policymakers. Extensive studies have been conducted on spatial-temporal distribution and variation of population aging in China [10,[20][21][22][23][24][25]. Huge spatial differences of the elderly population were found at the national level and provincial levels in China based on these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The overall national inequality, T, of a particular socioeconomic variable distribution, based on the powiat level, can be measured using the following formula [92,93]:…”
Section: Gs-gas Supplymentioning
confidence: 99%
“…Owing to its large land area, in regard to climate features, China could be divided into Northern or Southern regions with Northern parts of China being significantly colder than its Southern counterparts (Hua et al, 2008;Si et al, 2014). On the other hand, development studies often divide China into four geographical regions (Northeast, Central, East, West) that reflect common levels of socioeconomic development (Liu & Zhang, 2019;Wu et al, 2019). The Eastern regions fare better economically than their Central or Western counterparts, while the Western regions remain relatively more under-developed than the Central regions of China (He et al, 2017;Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%